1996
DOI: 10.3109/00365599609182310
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Specific Antigen and Benign Prostatic Hyperplasia

Abstract: The aim of this study on patients (n = 51) with urodynamically proven obstruction was to search for correlations between serological levels of prostatic specific antigen (PSA) and age of patients, volume of prostate and prostatic morphology as evaluated on transurethral resection specimens. No correlations could be found between PSA levels and morphological parameters such as degree of inflammation and relative degree of stromal or epithelial hyperplasia. Significant correlations were demonstrated between PSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In some group of people, mixed hyperplasia with equal proportions of both components can be observed, However any correlation between this type of hyperplasia, and serum PSA level has not been detected. [9] Serum PSA level is very important for urologists. Indeed prostate cancer (PCa) is the most frequently type of cancer encountered in men in Europe, and the USA.…”
mentioning
confidence: 99%
“…In some group of people, mixed hyperplasia with equal proportions of both components can be observed, However any correlation between this type of hyperplasia, and serum PSA level has not been detected. [9] Serum PSA level is very important for urologists. Indeed prostate cancer (PCa) is the most frequently type of cancer encountered in men in Europe, and the USA.…”
mentioning
confidence: 99%
“…Kefi et al [14] reported that there was no difference between the patients with and without AUR with respect to prostatic volume and the weight of resected prostatic tissue; however, there was a significant difference with respect to the tPSA level. Tuncel et al [15] and Atan et al [16] also found that the serum tPSA level was an important risk factor in AUR etiology, whereas the prostatic size was not. Our findings were opposite to theirs, both in terms of tPSA and Rt.…”
Section: Discussionmentioning
confidence: 99%